2020
DOI: 10.1007/jhep06(2020)140
|View full text |Cite
|
Sign up to set email alerts
|

The black hole weak gravity conjecture with multiple charges

Abstract: We study the effect of higher-derivative corrections on asymptotically flat, fourdimensional, dyonic black holes in low-energy models of gravity coupled to N U(1) gauge fields. For large extremal black holes, the leading O 1/Q 2 correction to the extremality bound is calculated from the most general low-energy effective action containing operators with up to four derivatives. Motivated by the multi-charge generalization of the Weak Gravity Conjecture, we analyze the necessary kinematic conditions for an asympt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…References [10,11] have recently shown that one-loop contributions to the Wilson coefficients generically lead to the weak form of the WGC being satisfied in the deep IR. It would be interesting to investigate this argument with the exponential coupling of the dilaton considered here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…References [10,11] have recently shown that one-loop contributions to the Wilson coefficients generically lead to the weak form of the WGC being satisfied in the deep IR. It would be interesting to investigate this argument with the exponential coupling of the dilaton considered here.…”
Section: Discussionmentioning
confidence: 99%
“…where M represents the black hole's mass and Q e , Q m , and Q ϕ represent its electric, magnetic, and scalar charges, respectively. The weak version of the WGC has been demonstrated, under some assumptions, 1 in Einstein-Maxwell theory [8][9][10][11]. See also [12][13][14][15][16][17][18][19][20][21] for more discussions of the conjecture.…”
Section: Introductionmentioning
confidence: 99%
“…The statement that black holes can always decay through these higher-derivative corrections is sometimes called the "Black Hole Weak Gravity Conjecture." This idea has inspired a large amount of work [5][6][7][8][9][10][11] on bounding the EFT coefficients, thereby proving the conjecture. While no existing proof is completely general, the work so far covers a large number of possibilities and assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that d 0 , the combination which is related to the WGC, enters the T = 0 entropy shift with the opposite sign as the constant m entropy shift of [19]. Furthermore, consider that for magnetic black holes, ∆m ∼ −(d 0 + 2d 6 ) [9] (see appendix also). Therefore enforcing the WGC (or alternatively, the positivity of the fixed-mass entropy shift) for all charged black holes in 4d tells us…”
Section: Positivitymentioning
confidence: 99%
“…Recently there has been a lot of progress on understanding if the required inequality does indeed hold using diverse arguments including consistency of the S-matrix [4][5][6][7], RG running [8][9][10], modular invariance [11], the c-theorem [12], and investigating various specific examples [13][14][15] and consequences [16][17][18]. A particularly intriguing argument [19] is that the combination of EFT coefficients which appears in the WGC calculation of [2] is (−1) times the same combination that appears in the shift to the black hole entropy at extremality.…”
Section: Introductionmentioning
confidence: 99%